2017
DOI: 10.3991/ijim.v11i5.6879
|View full text |Cite
|
Sign up to set email alerts
|

Students' Attitudes Towards the Use of Mobile Technologies in e-Evaluation

Abstract: Abstract-Mobile learning (M-learning) is a new wave in the era of educational technology that provides informal, personal, voluntary, and situated learning opportunities for both learners and educators. Mobile-based assessment is one of the emerging technologies that attract many scholars to investigate its effectiveness due to the wide spectrum of its features like portability, interactivity, flexibility, and ubiquity. Based on the surveyed literature, we noticed that there is a lack of studying the students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…This result is in agreement with the results revealed by [21]. On the other side, these results contradict with other studies like [22], [23], in which these studies did not reveal any significant difference between the students' genders. With regard to the second research question which concerns about measuring the students' attitudes towards the use of M-learning with regard to smartphone ownership, the results revealed that those who own smartphones were more positive than those who don't towards the use of M-learning.…”
Section: Discussionsupporting
confidence: 85%
“…This result is in agreement with the results revealed by [21]. On the other side, these results contradict with other studies like [22], [23], in which these studies did not reveal any significant difference between the students' genders. With regard to the second research question which concerns about measuring the students' attitudes towards the use of M-learning with regard to smartphone ownership, the results revealed that those who own smartphones were more positive than those who don't towards the use of M-learning.…”
Section: Discussionsupporting
confidence: 85%
“…As 61% of individuals had a bachelor's degree, 24% had a master's degree, while the rest of 15% of the respondents had a doctoral degree. The "purposive sampling approach" was used when the respondents are accessible easily and are ready to volunteer, as suggested by [48]. The sample was composed of students from various backgrounds, colleges, and ages, belonging from diverse programs at different levels.…”
Section: Students' Personal Information/demographic Datamentioning
confidence: 99%
“…In addition, the participation of a limited number of students (372) is another limitation. According to [45], a survey questionnaire method was used for data collection. For appropriate and improved outcomes, an enhanced instrument is being sought and more institutes will be taken into account from other regions, such as the Arab Gulf, including Kuwait, Saudi Arabia, and Bahrain.…”
Section: Limitations and Further Researchmentioning
confidence: 99%